Cortical AAV-CNTF Gene Therapy Combined with Intraspinal Mesenchymal Precursor Cell Transplantation Promotes Functional and Morphological Outcomes after Spinal Cord Injury in Adult Rats - Stuart I. Hodgetts; Jun Han Yoon; Alysia Fogliani; Emmanuel A. Akinpelu; Danii Baron-Heeris; Imke G. J. Houwers; Lachlan P. G. Wheeler; Bernadette T. Majda; Sreya Santhakumar; Sarah J. Lovett; Emma Duce; Margaret A. Pollett; et al. (Neural Plasticity)
Ciliary neurotrophic factor (CNTF) promotes survival and enhances long-distance regeneration of injured axons in parts of the adult CNS. Here we tested whether CNTF gene therapy targeting corticospinal neurons (CSN) in motor-related regions of the cerebral cortex promotes plasticity and regrowth of axons projecting into the female adult F344 rat spinal cord after moderate thoracic (T10) contusion injury (SCI). Cortical neurons were transduced with a bicistronic adeno-associated viral vector (AAV1) expressing a secretory form of CNTF coupled to mCHERRY (AAV-CNTFmCherry) or with control AAV only (AAV-GFP) two weeks prior to SCI. In some animals, viable or nonviable F344 rat mesenchymal precursor cells (rMPCs) were injected into the lesion site two weeks after SCI to modulate the inhibitory environment. Treatment with AAV-CNTFmCherry, as well as with AAV-CNTFmCherry combined with rMPCs, yielded functional improvements over AAV-GFP alone, as assessed by open-field and Ladderwalk analyses. Cyst size was significantly reduced in the AAV-CNTFmCherry plus viable rMPC treatment group. Cortical injections of biotinylated dextran amine (BDA) revealed more BDA-stained axons rostral and alongside cysts in the AAV-CNTFmCherry versus AAV-GFP groups. After AAV-CNTFmCherry treatments, many sprouting mCherry-immunopositive axons were seen rostral to the SCI, and axons were also occasionally found caudal to the injury site. These data suggest that CNTF has the potential to enhance corticospinal repair by transducing parent CNS populations.